Use of Telehealth in Outpatients Settings During the Pandemic Covid-19: A Literature Review - Wiwin Sulistyawati; Indah Jayani; Susmiati Susmiati; Endang Mei Yunalia; Arif Nurma Etika (Journal for Quality in Public Health, 2020)
Background: In the covid-19 pandemic, physical distancing has been necessary to help prevent disesase transmission. This makes outpatients afraid and worried about going to the hospital. Telehealth is one of the solutions for treating patients in the covid-19 pandemic. Telehealth helps patients consult with health professionals to get a cure. The application of telehealth in outpatient services is carried out by several methods. Purpose: The purpose of literature review is to identify the telehealth method used in outpatients during covid-19 pandemic. Methods: The data base used in making this review of literature are Science Direct, Ebscohost and Google Scholar published in 2020. This literature review searched for studies with the keyword “Telehealth” or “Telemedicine” or “Outpatients” or “Covid-19 pandemic” and selected 4 articles from electronic database. Results: The results of the study found several telehealth methods used in outpatients during covid-19 pandemic such the virtual orthopedic examination, virtual telemonitoring covid-19 clinic for obstetric patient, telemedicine for neuro oncology patient and facial plastic surgery.Conclusion: Telehealth is an appropriate methode of health care used in outpatients during the covid-19 pandemic to reduce and prevent covid-19 transmission.